Combined effects of carotid plaques and hypertension on the risk of cardiovascular disease and all‐cause mortality. Issue 7 (12th May 2020) - Li, Wen; Zhao, Jianqiu; Song, Lu; Chen, Shuohua; Liu, Xuemei; Wu, Shouling
Abstract: Background: Both hypertension and atherosclerotic plaques are risk factors for cardiovascular disease (CVD). Hypothesis: This study aimed to investigate whether the combined effects of carotid plaques and hypertension increase the risks of CVD and all‐cause mortality. Methods: Patients from the stroke and elderly cohorts of the Kailuan study in China who completed a carotid sonography examination were included in the study. Participants in both cohorts underwent physical examinations between 2010 and 2011 and were divided into four groups: no carotid plaques with normal blood pressure (n = 2227), hypertension only (n = 1290), carotid plaques only (n = 1128), and hypertension with carotid plaques (n = 1862). The outcomes included the first occurrence of CVD and all‐cause mortality. Results: Among the 6507 participants (mean age, 58.1 ± 11.8 years, 61% males), 157 cardiovascular events, and 210 deaths occurred after average follow‐ups of 4.5 and 4.9 years, respectively. After adjusting for covariates, carotid plaques only and hypertension with carotid plaques were associated with excess risk (hazard ratio [HR]; confidence interval [CI]) for the first occurrence of CVD (HR = 1.85; 95% CI, 1.01‐3.44; and HR = 2.97; 95% CI, 1.66‐5.29, respectively), cerebral infarction (HR = 2.66; 95% CI, 1.16‐6.15; and HR = 4.15; 95% CI, 1.87‐9.19, respectively), and all‐cause mortality (HR = 1.96; 95% CI, 1.16‐3.31; and HR = 1.85; 95% CI, 1.09‐3.13, respectively). Conclusions: The combination of hypertension and atherosclerotic plaques may increase the risk of CVD events and all‐cause mortality, especially cerebral infarction, compared with participants without those factors.